An empirical study of it innovation adoption among small and medium size enterprise in Malaysia - Moghavvemi, S.; Mohd Salleh, N.A.; Zhao, W.; Hakimian, F. (2011)
This study used Entrepreneurial Event model as a base model to investigate SME owners’ perception toward IT innovation adoption and use. Since this model investigates the individual’s intention toward taking action, it would be interesting to test and validate this model in an individual’s intention toward technology acceptance. This study revised and validated the model in a new context and tried to examine the effect of perceived desirability, propensity to act and performance expectancy on behavior intention to adopt and use IT innovation in SMEs companies. Questionnaires were distributed to collect data from Malaysian industries in Kuala Lumpur. 412 completed questionnaires were available in this study, and SEM techniques were applied for data analysis. Results showed that perceived desirability, propensity to act and performance expectancy have a significant positive influence on behavioral intention, and also found that experience moderated the relationship between determinants and behavior intention.